A Note on Prevalence of Theileriaannulata and Nutritional Status in Crossbreed Cows - Dadhich, Ram; Mehta, Hemant Kumar; Gupta, Arup Kumar; Jain, Raj Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The objective of the present study was to relatethe prevalence of T.annulata and nutritional status of the animals. The animals having good nutritional status suffer least from ticks infestation in all age group of animals ie calves up to 1 year, heifers from 1 to 3 years and adult cows more than 3 years having good nutritional condition, the prevalence of T.annulata was found to be least whereas the prevalence of T.annulata was found to be more in the animals having poor nutritional status. The study showed that as the nutritional status becomes poor prevalence of T.annulata increased substantially.
Keywords: :Theileria; Nutritional statu; crossbred cow; Prevalence